Pengaruh Pembelajaran Daring terhadap Prestasi Belajar IPS Siswa Kelas VIII MTs. Al Azhar Pagelaran - Hendra Rustantono; Kholilur Rohman (IKIP PGRI Bojonegoro, 2022)
Abstrak: This research is motivated by the existence of a policy from the Ministry of Education and Culture (Kemendikbud) regarding the implementation of home learning activities carried out in a bold way (on the network). Many problems were encountered when implementing the brave system, such as internet network problems, lack of student interest, etc. Therefore, the author is interested in researching the effect of bold learning on social studies learning achievement for class VIII students at Mts. Al Azhar Pagelaran. The purpose of this study is to determine the effect of learning courage on social studies learning achievement in class VIII students at MTs. Al Azhar Pagelaran. The type of research used in this research is descriptive quantitative research method. The population of this study were all students of class VIII in MTs. Al Azhar Pagelaran. In collecting data, researchers used research instruments, namely observation, documentation, questionnaires, and interviews. The results of the study explain that the acquisition value of SPSS 25 for windows is for tcount (4.507) > ttable (1.683) and the significance value (0.000) < (0.05) which means HO is rejected and Hɑ is accepted. So it can be stated that learning in the network affects the social studies learning achievement of class VIII students in MTs. Al-Azhar Pagelaran Malang, meaning that the better students participate in bold learning activities, the higher the social studies learning achievement that will be obtained. Abstrak: Penelitian ini dilatarbelakangi oleh adanya kebijakan dari Kementrian Pendidikan dan Kebudayaan (Kemendikbud) mengenai diberlakukannya pelaksanaan kegiatan pembelajaran dari rumah sehingga pembelajaran dilakukan dengan cara daring (dalam jaringan). Banyak permasalahan yang ditemui saat diterapkannya sistem daring, seperti kendala jaringan internet, kurangnya minat siswa, dll. Oleh kerena itu penulis tertarik untuk meneliti mengenai pengaruh pembelajaran daring terhadap prestasi belajar IPS siswa kelas VIII di Mts. Al Azhar Pagelaran. Tujuan dari penelitian ini yaitu untuk mengetahui pengaruh pembelajaran daring terhadap prestasi belajar IPS pada siswa kelas VIII di MTs. Al Azhar Pagelaran. Jenis penelitian yang digunakan pada penelitian ini adalah metode penelitian kuantitatif deskriptif. Adapun populasi penelitian ini adalah seluruh siswa kelas VIII di MTs. Al Azhar Pagelaran. Dalam pengempulan data, peneliti menggunakan instrumen penelitian yaitu observasi, dokumentasi, angket, dan wawancara. Hasil penelitian menjelaskan bahwa nilai perolehan perhitungan SPSS 25 for windows untuk nilai thitung (4,507) > ttabel (1,683) dan nilai signifikansi (0,000) < ɑ (0,05) yang artinya HO ditolak dan Hɑ diterima. Maka dapat dinyatakan bahwa pembelajaran dalam jaringan (daring) berpengaruh terhadap prestasi belajar IPS siswa kelas VIII di MTs. Al-Azhar Pagelaran Malang, artinya semakin baik siswa dalam mengikuti kegiatan pembelajarn daring maka akan semakin tinggi pula prestasi belajar IPS yang akan didapatkan.